Human factors validation study of 3 mg sumatriptan autoinjector, for migraine patients - Brand-Schieber E (Dove Medical Press, 2016)
Elimor Brand-Schieber,1 Sagar Munjal,1 Rajesh Kumar,1 Anthony D Andre,2 Will Valladao,2 Margarita Ramirez2 1Dr. Reddy’s Laboratories Inc., Princeton, NJ, 2Interface Analysis Associates, Saratoga, CA, USA Background: Migraine pain relief is reported by more than 50% of patients who receive low dose (3 mg) of sumatriptan. Currently, there is no two-step autoinjector of low-dose sumatriptan available on the market for acute migraine treatment. To fulfill this need, a fully assembled, single-dose, subcutaneous autoinjector (sumatriptan 3 mg; product-code DFN-11) was developed. The device allows for injection with a simple two-step, push-to-inject process and provides feedback of the injection activation, progress, and completion.Objective: To determine if DFN-11 autoinjector can be used correctly and safely by migraine patients.Methods and participants: A human factors validation study was conducted with 45 migraine patients (30 oral-only medications users; 15 injectable sumatriptan users) who performed one unaided simulated injection. Two days prior, half the oral participants were briefly trained. All others were only given the device to inspect and written instructions to review. No injections were performed during the initial session. All participants received written instructions at the injection session.Results: All participants (45/45; 100%) performed the injection without any errors. Objective measures included device removal from packaging, cap removal, expiration date check, inspection of fluid in window, identification of allowable injection site, proper device positioning, dose confirmation, and device disposal. All participants (45/45; 100%) reported no difficulty administering the injection and no concerns about using the autoinjector during a severe migraine onset.Conclusion: The results showed that the DFN-11 autoinjector can be used with safe handling without patterns of confusion, failures, high-risk errors, wet injections, or patient safety risks. The DFN-11 autoinjector was validated to be used correctly and safely by migraine patients, whether they were injection experienced, unexperienced, trained, or self-trained. Keywords: triptan, pain relief, subcutaneous injection, preference, usability